Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Intervening (Studi Kasus pada Karyawan Kanca Bank Syariah Indonesia Palembang) - Nuri Annisa Fitri; Hisbullah Basri; Ima Andriyani; Nur Even (UNIVED Press, 2023)
This study aims to determine the effect of leadership style on employee performance with work motivation as an intervening variable (study on employees of Bank Syariah Indonesia Palembang branch office). The respondents of this study were 26 people. This study uses two testing methods, namely simple regression analysis and Sobel Test. The first hypothesis, the calculated F value is 0.118 with a Sig value. = 0.734 > 0.05. That is, there is no significant influence of leadership style on employee performance. The second hypothesis, in the first test, the significance value of the Leadership Style variable is 0.070 (> 0.05). So it can be concluded that leadership style has no significant effect on work motivation. Based on the Sobel Test, the a value is -0.412, the b value is 0.620, the Sa value is 0.0218, the Sb value is 0.158. The Test Statistic value is -1.702 and the P-Value is 0.088. That is, there is no significant effect of Leadership Style on Employee Performance with Work Motivation as an Intervening Variable.